An innovative online HIV/STI prevention programme in Higher Education: Preliminary Results NMMU - Steenkamp, Liana; Busolo, Mellanda; von der Marwitz, Jill (South African Journal of Higher Education, 2016)
The objectives were to determine risky sexual behavioural trends and health promotion needs among students, to develop an online HIV/STI prevention programme utilising the NMMU intranet portal. Descriptive data regarding demographics, sexual behaviour, internet usage and the relevance of various health promotion messages were included in an online questionnaire. Participants’ attitude towards risk behaviour was also assessed using ten outcome questions rated on a five-point Likert scale. Of the 428 students participating in the survey during November 2011, 83% reported to be sexually active, 50% reported using a condom during the last time of sexual intercourse, while 43% reported more than two sexual partners during the past 12 months, reflecting high risk behaviour. The topic “How to convince your partner to use a condom” was rated “very important” by 72% of the sample. Study outcomes are being incorporated into an online HIV/STI prevention programme developed in collaboration with NMMU students.